La grève : ses facteurs déterminants et son effet sur les hausses de salaire. Une synthèse critique - Lacroix, Robert; Dussault, François (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
This article is a critical survey of the literature on strike activity. Its first part deals with the various explanations of strike activity and concludes that the effect of economic variables on strike activity is theoretically indeterminate. The second part of this text tackles the question of the effect of strike on wages and concludes that the theoretical foundations of this effect are doubtful.